Socioeconomic predictors of preventive health check-ups by a general practitioner in the Czech Republic - Jarmila Zimmermannova; Jiri Vevoda; Tereza Schovankova; Ondrej Holy (Frontiers in Medicine)
Health is one of the Sustainable Development Goals. The importance of health promotion is growing in the context of an aging population and increasing life expectancy. Prevention is often underestimated and neglected by citizens. This article aims to identify the socioeconomic predictors of preventive health check-ups by general practitioners in the Czech Republic, focusing on selected age groups. An original dataset is prepared based on data for 2010–2019 provided by the largest health insurance company in the Czech Republic, the General Health Insurance Company. Correlation and regression analysis methods are used to achieve the objectives. Two models are built and tested: (1) preventive examinations model and (2) preventive examinations in age group 65+ model. Based on the results, preventive medical examinations in the pensioner group depended on economic indicators, such as the average wage, employment, and gross domestic product, in the analyzed period. For the total population, overall population size, the average age, urbanized area, and level of education play a key role. The results reveal a difference between the general population group and the 65+ population group. Government interventions and health policies promoting prevention should consider using appropriate incentive policy instruments targeting the 65+ population to prolong active life in senior age.